Subclinical Hypothyroidism in Overweight /Obese Children in Pediatric Clinic of Tishreen University Hospital in Lattakia - فحام محمد ناجي; محمد عماد خياط; أحمد شريتح (Latakia University Journal -Medical Sciences Series, 2022)
Background: Subclinical hypothyroidism is biochemically defined as an elevated serum thyrotropin level (TSH) in combination with a serum free T4 is within the reference range. Many patients with subclinical hypothyroidism are asymptomatic. Overweight and obesity are defined as abnormal or excessive fat accumulation that may impair health. Body mass index (BMI) is a simple index of weight-for-height that is commonly used to classify overweight and obesity. Aim: We aimed to examine the prevalence of subclinical hypothyroidism among healthy weight, overweight and obese children. Determine the relationship between subclinical hypothyroidism and BMI, age and sex. Materials and Methods: This study is a cross sectional study conducted at Tishreen University Hospital, Lattakia, Syria during the period between May 2020 and May 2021. The study included 204 children (100 healthy weight, 19 overweight, 85 obese), aged 2-13 years. Weights and heights were measured and BMI calculated. Thyroid function tests TSH and free T4 (if TSH was elevated) were assessed in all subjects. Results: The prevalence of subclinical hypothyroidism were (4% in healthy weight, 10.5% in overweight, 16.5% in obesity). Serum TSH level was significantly higher in (obese 3.40 mUŁ) compared to (overweight 2.31 mUŁ) and (healthy weight 2.10 mUŁ) P-value = 0.0001, with no significant difference in serum FT4 levels between the groups (1.42 ng/dl in obese, 1.65 ng/dl in overweight, 1.70 ng/dl in healthy weight. P-value = 0.05). There was a positive correlation between BMI and TSH (as BMI increases, TSH levels increase) with a statistical difference (Pearson correlation r = 0.4, P-value = 0.04). There were no significant differences in demographic variables between the groups. Conclusion: The prevalence of subclinical hypothyroidism was higher among overweight/obese children. TSH levels were found to be higher in obese children with positive correlation between BMI and TSH. There was no significant difference in FT4 levels between the groups.